Specifics of Using C.G. Jung’s Archetypes in Business Consulting Activities: Myths and Reality - REXHEPI, Burhan Reshat; MUSTAFA, Labeat; SADIKU, Mejreme Krasniqi; BERISHA, Burim Isa; XHAFERI, Besa Seadin; REXHEPI, Orhan Reshat (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
A trend of accelerated production and, consequently, consumption has led to the growing role of marketing in business consulting activities. The relevance of this research is conditioned upon the crisis in the marketing sphere, the inability of marketers to understand consumers in the era of market saturation, and the great significance of the practical application of C.G. Jung’s archetypes to express brand identity. The purpose of this research is to identify the specifics of using Jung archetypes in business activities, to identify specific valid archetypes that can personalise a brand, to debunk myths regarding the effectiveness of using Jung’s theory. The theoretical foundation of the research is Jung’s archetypes model, further research and applied scientific developments of scientists, were devoted to the problem of archetypes theory and their application to increase the effectiveness of branding. The methodological approach is based on a qualitative combination of modelling and system analysis methods. The main results obtained in the framework of this scientific research should be considered the identification of specific valid Jung archetypes for improving the effectiveness of business consulting activities, exposing myths and reality in the outdated theory of archetypes, identifying ways and means of developing archetypes on the example of specific brands. The results of this scientific research and the conclusions bear significant significance for employees of the marketing sphere. The article identifies the cultural influence on the brand archetype, which is an essential criterion for marketers, economists and generalists when choosing a business marketing strategy.